Optimizing Heat Dissipation in Permalloy Wire-Tube Nanostructures: A Pathway to Improved Hyperthermia Treatments - Escrig-Murua, J; Saavedra-Díaz, E (American Institute of Physics, 2025)
This work investigates the heating efficiency of permalloy wire-tube nanostructures through micromagnetic simulations. We demonstrate that specific geometrical configurations of these nanostructures enhance their heating capacity compared to conventional nanowires. This improvement is attributed to the optimized control of dynamic magnetization processes, which directly influence the specific absorption rate. Our findings provide valuable insights into designing advanced nanostructures with improved heating performance, paving the way for more efficient and minimally invasive magnetic hyperthermia treatments in cancer therapy. Additionally, the geometric tunability of wire-tube nanostructures underscores their potential for targeted biomedical applications, where precise thermal delivery is critical. © 2025 Author(s).